Understanding Digital Logistics Adoption in an Indonesian Food-Based SME: A Qualitative Exploration of Operational Efficiency and Logistics Coordination - Aisyah Indarsari; Febrina Hambalah (International Journal Labs, 2026)
Digital transformation has become an essential strategy for small and medium-sized enterprises (SMEs) to improve operational performance, responsiveness, and competitiveness in the Industry 4.0 era. In food-based SMEs, logistics activities require effective coordination, accurate inventory management, and rapid information exchange to address dynamic customer demands. However, many SMEs continue to face limitations in technological readiness, financial resources, and operational infrastructure, resulting in gradual digital adoption. This study aimed to explore how digital logistics practices were adopted by an Indonesian food-based SME and how these practices contributed to operational efficiency and logistics coordination. This research employed a qualitative descriptive approach using semi-structured interviews and operational observations. Data were collected from five informants consisting of the business owner, warehouse staff, online sales administrator, distribution administrator, and inventory personnel. Thematic analysis was applied to identify patterns related to digital logistics adoption, operational efficiency, coordination processes, challenges, and future expectations. The findings revealed that the SME utilized accessible digital tools, including WhatsApp, Google Sheets, Shopee, TikTok Shop, and WhatsApp Business, to support inventory monitoring, order management, communication, and distribution activities. These digital practices improved information flow, inventory visibility, operational responsiveness, and coordination efficiency. However, challenges remained regarding budget constraints, employee adaptation, technology integration, and infrastructure readiness. This study concluded that practical digital logistics adoption could enhance SME operational performance while highlighting the need for more integrated and automated digital systems in the future.